REVIEW ON SALT-AFFECTED SOILS STUDIES IN SUDAN - Awadelkarim, Elfatih E.; Elgubshawi, A.I.; Sulfab, Hatim A. (IJRDO-Journal of Agriculture and Research (ISSN: 2455-7668), 2017)
Salt-affected soils in the Sudan fall under three soil orders: Vertisols, Aridisols and Entisols; in a vast area between 14 and 22 latitudes’ covering an area of about 4.874 million hectares; only 268636 hectares were mapped till 2007.Soil salinity occurs at soil depths of 30-60 cm, often associated with sodicity, the most commonly salts found are sodium chlorides and sodium sulphates. Comprehensive studies on physical and chemical properties of salt-affected soil the reclamation and management were undertaken by many research workers in Sudan. The Relative hydraulic conductivity (RHC) of a salt-affected soil decreases with ESP increases as C decreases; and at a given ESP, RHC increases as C increases; DI increases with increasing ESP and decreasing C. The use of 5 and 10 tons gypsum/ha in ASSPC reduced the ESP from 18 to 5.5 and 7.3 and the ECe from 4.2 to 1.2 and 2.2 dS/m and significantly increased wheat grain yield from 1141 to 1739 and 1926 kg/ha, respectively. Application of organic and/or chemical fertilizers is very essential for crop production in high terrace soils especially wheat. In addition to 2N, the use of 5 tons FYM/ha plus 1P followed by 10 tons FYM/ha without P is recommended as a package for wheat promotion in the high terrace soils of Nile River. In another study, and in addition to a basal dose of 2N + 1P, the use of two tons CHM/ha was recommended for wheat production as another option package to 5 tons FYM/ha + 2N + 1P. Phosphorus fertilization and P and K interaction significantly increased growth attributes and dry matter of forage sorghum. Application of 2N NPK to wheat in EHRF resulted the highest wheat grain yield (2979 kg/ha) compared with other DNS. In another study and in the same site, the use of 1N NPK topped by 1N ASN gave the highest wheat grain yield (2935 kg/ha). Dry matter yield of forage sorghum increased significantly with increase of nitrogen level, with decrease in irrigation interval and with gypsum application. Watering of lucerne every 7 days with addition of CHM was found superior treatment among others treatments (gypsum, Sulfur, dry sewage, CHM plus gypsum).